(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A cross sectional descriptive study was conducted within Ilala Municipality in Dar es Salaam, Tanzania. A structured questionnaire was used for data collection. A total of 196 community members were recruited into the study. The participants were asked to provide information on what drugs they took when they had pain and if they knew any adverse effects associated with the use of non-steroidal antiinflammatory drugs. They were also asked if they had been given any education by health personnel on the adverse effects of non-steroidal anti-inflammatory drugs. Fifty two percent of the participants responded that when they had pain, they bought pain killers from pharmacies while 42% said they would go to hospital for treatment. About 4% drank a lot of water when they had a headache, while 1% performed massage at the site of pain. One percent visited traditional healers to seek treatment for the pain. Only 8% of the study participants knew some adverse effects caused by non-steroidal anti-inflammatory drugs. Hence, there is a need for health personnel to educate patients on the potential adverse effects of the nonsteroidal anti-inflammatory drugs.